1980
DOI: 10.1002/dev.420130109
|View full text |Cite
|
Sign up to set email alerts
|

The effects of litter size on the expressivity of the jaundice genotype in gunn rats

Abstract: In 2 studies Gunn rats carrying 2 recessive alleles for jaundice (jj) were compared with their heterozygous littermates (Jj) under varied litter size (4 vs 12 pups) and handling conditions. Handling did not produce long-term effects. Litter size interacted with Genotype to increase the differential response of jj rats by 21, 23, and 50 days of age. A decrease in survival rates and weight gain was found in Jj and especially jj rats from large litters. For jj rats only, being reared in a large litter increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The fact that we did not detect significant differences in stride length or other gait parameters in our 9–10 month-old group was surprising, but consistent with studies that have quantified gait in this model ( 29 ). Although other groups have reported a wobbly gait or ataxia in young Gunn rats ( 15 , 30 , 31 ), these reports have been observational. We also observed and quantified a wobbly gait in some, but not all, of the younger Gunn rats in our study (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…The fact that we did not detect significant differences in stride length or other gait parameters in our 9–10 month-old group was surprising, but consistent with studies that have quantified gait in this model ( 29 ). Although other groups have reported a wobbly gait or ataxia in young Gunn rats ( 15 , 30 , 31 ), these reports have been observational. We also observed and quantified a wobbly gait in some, but not all, of the younger Gunn rats in our study (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…A new Sprague-Dawley strain of Gunn rats developed in our laboratory Keino et al, 1985-6) was used at 5, 8, 10, 15, and 20 days of life. Soon after delivery, the litter size of newborns was reduced to eight so that environmental factors, which might affect cerebellar growth (Graham et al, 1978), were minimized. Homozygous ( j j ) and heterozygous ( j + ) rats were allotted to experimental and control groups, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Mutant homozygotes broadly fell into two populations, being either nominally healthy (notwithstanding their tendency to being underweight compared with siblings, see Gunn (1944) for the first description of this), or moribund -this is in marked contrast to the six-point clinical rating scale described by Spencer et al (2002). Pups, particularly from larger litters would fail to thrive and enter a vicious downward spiral from around P10 to weaning age, at around 3-4 weeks (also described by Graham et al (1980). They would become irritable, hyperactive (Stanford et al, 2015) and hypervocal (Lenhardt, 1982) followed by a descent into lethargy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%